Comparison of the effects of bio-based and mineral fertiliser use on heavy metals dietary exposure in six European countries - Domínguez Carrasco, María D. R.; Salo, Tapio; Keskinen, Riikka; Suomi, Johanna (Agricultural and Food Science, 2025)
This study compared the effects of using bio-based fertilisers (BBFs) of high (BBFH) or low (BBFL) metal content with conventional mineral superphosphate (SP) fertilisation on dietary exposure of arsenic (As), cadmium (Cd), nickel (Ni) and lead (Pb), in Finland, Denmark, France, Germany, Hungary, and Spain. We estimated changes in the metal content of the following crops: wheat, barley, oat, rye, potato, carrot, sunflower seed, and maize following 100-year scenarios of fertilization with the different products. To estimate changes in chronic dietary exposure to metals via food, we used available national data of food consumption and metal content in target crops. Our results showed low changes to current chronic dietary exposure after using BBFs. Exceedance of the maximum allowed levels of Cd and Pb in food (EU 2023/915) was more rare with low-Cd BBF than with SP mineral fertilizer. Only the BBFH slightly increased the dietary exposure to Cd, although similarly to SP. In conclusion, the studied BBFs did not increase dietary exposure to heavy metals, especially compared with the use of conventional SP mineral fertiliser.